DETERMINATION OF SUITABLE THIN-LAYER DRYING MODELS FOR BREWER’S YEAST (Saccharomyces cerevisiae) - Mendieta, Rolando; Haerinejad, Masoud; Picado, Apolinar (Nexo Revista Científica, 2017)
Mathematical models of thin-layer drying for brewer’s yeast (Saccharomyces cerevisiae) were studied and verified with experimental data. Twelve (12) different mathematical drying models were compared according to three (3) statistical parameters, i.e., correlation coefficient, root mean square error and chi (χ²)-square. The thin-layer drying kinetics of brewer’s yeast was experimentally investigated in a laboratory tunnel dryer and the mathematical modelling, using thin-layer drying models present in the literature, was performed. Experiments were performed at air temperature of 40, 50 and 60 ºC at an airflow rate of 1.2 m/s. Drying curves obtained from the experimental data were fitted to the thin layer drying models. The results show that the Page model is the most appropriate model for predicting the drying behaviour of the thin-layer brewer’s yeast.